Experience and representations of the natural world in an Andean community of Cajamarca - De La Torre A., Ana (1985)
In this article some aspects of the conceptual organization of the natural world in a peasant community of the Northern highlands of Peru are exposed. First, the classificatory categories used as organizing criteria for the multiplicity of the sensible world in the aspect of Flora are presented. Then the collective representations that emerge as ideological elaborations based on the organization of sensible experience are exposed.